FAMILY-FRIENDLY POLICIES TERHADAP WORK-FAMILY CONFLICT SERTA IMPLIKASINYA PADA KOMITMEN KARYAWAN - -, SURVIVAL -; NURHAYATI, INDAH DEWI (JURNAL MANAJEMEN DAN AKUNTANSI, 2013)
Abstract: The objectives of this study is to find out the influence of family-friendly policies on work-family conflict, the influence of work-family conflict on employee commitment, the influence of family-friendly policies on employee commitment, the influence of family-friendly policies on employee commitment mediated work-family conflict. This type of research is an explanatory study. A survey technique using questionnaire with likert scale as the instruments of research to collect the data. the technique used for selecting the sample was purposive sampling. The number of respondents being observed was 75 people. The statistic analysis tool for testing the hypothesis was used path analysis method to find out the relationship among the variables. The result of this study finding are: 1) the family-friendly policies significantly influences the work-family conflict; 2) the work-family conflict significantly influences the employee commitment; 3) the family-friendly policies significantly influences the employee commitment; 4) the family-friendly policies insignificantly influences the employee commitment mediated work-family conflict. Key words: family-friendly policies, work-family conflict, employee commitment